Effect of Work Rotation on Job Satisfaction - Dedi Hadian (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2019)
Find out the performance of employees, and it is necessary to measure or evaluate performance criteria. One assessment of employee work is job satisfaction determined by job rotation. Based on the phenomenon in the field, this study aims to assess the effect of job rotation on job satisfaction. This study uses a survey approach to employees. Structural analysis of equation modeling used to analyze data. The results of the survey prove that job rotation, which consists of additional employee capabilities, other employee knowledge, and overcoming employee saturation levels, affects job satisfaction.